Application of Distributed Hydrological Model Based on NRIHM in Humid Watershed - XU Qin; LIU Lulin; LONG Jie; JIN Chen; CAI Jing; LIN Xiaoqing; ZHANG Kun (Renmin Zhujiang)
The distributed hydrological model is the development trend of hydrological models. The model of Nanjing Research Institute of Hydrology (NRIHM) is a lumped hydrological model with a flexible architecture. In order to explore the feasibility and adaptability of using a distributed hydrological model based on NRIHM to carry out hydrological simulation in the humid watershed, the Nandawa-Shahe nested watershed in the humid area was studied. Firstly, based on the construction idea of the NRIHM runoff generation model, a one-layer runoff generation model and a two-layer runoff generation model were constructed. The runoff generation simulation verification at the grid point scale was carried out by using the observation results of the natural experimental watershed. The simulation results were compared, and it was found that the two-layer parabola combination method had a better simulation effect. Based on this runoff generation calculation method, a distributed hydrological model with a two-layer soil structure was constructed. The application was carried out in the catchment area above the Shaheji Reservoir in the Chuhe River system of the Yangtze River. The average deterministic coefficients of the calibration period and the verification period were 0.80 and 0.86, respectively. The relative errors of average flood peak and flood volume were also less than 20 %, indicating that the model could better simulate the actual runoff process, which preliminarily proved that the model had good applicability in humid areas.